2014
DOI: 10.1016/s2215-0366(14)70307-4
|View full text |Cite
|
Sign up to set email alerts
|

Young adult sequelae of adolescent cannabis use: an integrative analysis

Abstract: Australian Government National Health and Medical Research Council.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
269
3
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 383 publications
(295 citation statements)
references
References 28 publications
15
269
3
8
Order By: Relevance
“…However, all participants were (near) daily users at baseline. It is therefore possible that variation in cannabis exposure is only associated with transition to dependence in younger and/or less experienced users, such as during adolescence (Silins et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, all participants were (near) daily users at baseline. It is therefore possible that variation in cannabis exposure is only associated with transition to dependence in younger and/or less experienced users, such as during adolescence (Silins et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study across three large samples found that cannabis use before the age of 17 was related to lower rates of high-school completion and degree attainment 50 . Similarly, a 1-year follow-up study of 1155 adolescents found that weekly cannabis use was related to poorer performance in GCSE Maths and English at age 16 (albeit less than tobacco), after controlling for confounders 51 .…”
Section: Cognition and Intelligencementioning
confidence: 99%
“…Engagement in risk behaviours such as tobacco, alcohol, cannabis and other illicit drug use has multiple negative health consequences, including respiratory problems, violence, injury, sexual risk behaviour, poorer educational attainment, psychosis, mental illness, risk of dependence, morbidity and mortality later in life 1, 2, 3, 4, 5, 6, 7. While the rate of substance use among young people in the United Kingdom is decreasing overall, a substantial proportion of young people continue to use these substances, with 31% of 16–24 year olds in the United Kingdom having ever used cannabis and nearly one‐fifth being regular or occasional smokers 8, 9.…”
Section: Introductionmentioning
confidence: 99%